From Interaction Flow Modeling Language to Symfony: an automated model transformation methodology - Sajji, Abir; Rhazali, Yassine; Hadi, Youssef (Bulletin of Electrical Engineering and Informatics, 2025)
Web application development has become increasingly complex with the rise of modern frameworks and user-centric architectures. Ensuring efficient and reliable development processes requires adopting structured methodologies that bridge abstract models with platform specific implementations. This paper presents a methodology for automating the transformation of Interaction Flow Modeling Language (IFML) models into Symfony models using the Atlas Transformation Language (ATL). The proposed approach supports model-driven architecture (MDA) principles and bridges the gap between abstract user interaction models in platform independent model (PIM) level and platform specific model (PSM) level. By leveraging IFML’s user-centered modeling capabilities and Symfony’s model-view-controller (MVC) framework, our solution enables the automatic generation of reliable, structured front-end architectures. Two case studies demonstrate the feasibility of the approach. This work contributes to the automation of model driven web development by offering a scalable and reusable transformation process from IFML to Symfony.